Relasi Budaya dan Agama dalam Perkembangan Agama Islam di Huta Sijungkang, Humbang Hasundutan - Herrio Tekdi Nainggolan (Institut Agama Kristen Negeri Tarutung, 2020)
AbstractThe space for interaction in society is always influenced by religion and culture as binding aspects, both individually and in groups. This study aims to reveal how the relationship between culture and religion in the development of Toba Islam in Huta Sijungkang, Parlilitan sub-district, Humbang Hasundutan district. The study was conducted with a qualitative approach through interviews and literature studies. Based on research conducted in the development of Islamic religion in Huta Sijungkang, culture and religion are not two contradictory entities, but an inherent unity to regulate relations in society. This has made the people not patterned based on religion, so that cultural and religious dualism is not a conflict, but rather a cultural identity and values that continue to be lived by the Huta Sijungkang community. For society, religious differences are not a barrier in family ties, so there is an awareness to maintain the principles of togetherness and unity.Keyword: Relation; Culture; Religion; Huta Sijungkang.